Application of Maillard reaction product of xylose–pea protein enzymatic hydrolysate in 3D printing. (2nd March 2020) - Zhou, Quancheng; Wang, Meng; Li, Hui; Wang, Sai; Sun, Wanting; Chen, Xuanhong; Dong, Leichao; Ruan, Zheng
Abstract: BACKGROUND: This paper aims to provide a basis for the application of Maillard reaction products and ideas for 3D printing of functional food. RESULTS: We evaluated the effects of pea protein enzymatic hydrolysate–xylose Maillard reaction products (xMRPs) on the printability of 3D printing materials and the structure using various techniques. It was found that compared with the addition of enzymatic hydrolysate, the materials with xMRPs and 3D printing could significantly improve the structure, physical properties, formability of 3D printing materials and 3D print products, among which the xMRPs with 6 g of xylose had the most significant effect. CONCLUSIONS: This study has important scientific value and practical significance for the high‐valued application of Millard reaction products and the promotion of the practical application of 3D printing technology in the food industry. © 2020 Society of Chemical Industry